Efficient Energy Conversion and Storage Based on Robust Fluoride‐Free Self‐Assembled 1D Niobium Carbide in 3D Nanowire Network. Issue 10 (6th April 2020) - Pang, Sin‐Yi; Io, Weng‐Fu; Wong, Lok‐Wing; Zhao, Jiong; Hao, Jianhua
Abstract: Owing to their high robustness and conductivity, 2D transition metal carbides and nitrides known as MXenes are considered as a promising material class for electrochemical catalysis, energy conversion, and storage applications. Nevertheless, conventional hazardous fluoride‐based synthesis routes and the intense intralayer bonding restrict the development of MXenes. Herein, a fluoride‐free, facile, and rapid method for synthesizing self‐assembled 1D architecture from an MXene‐based compound is reported. The MXene nanowire (NW) not only provides a robust connection to the flexible substrate but also effectively increases the electrochemically active surface area. The kinetics‐favorable structure yields a boosted performance for the hydrogen/oxygen evolution reaction and the intake of the zinc ion. The 1D NW based on MXene compound maintains high stability in a quite low overpotential of 236 mV for 24 h without detachment from the substrate and manifests an exceptional high‐power density of 420 W kg −1 over 150 cycles as a flexible aqueous zinc ion battery. This work paves a novel and non‐toxic synthesis method for the 1D nanofiber structure from MXene composition and demonstrates its multifunctional applications for energy conversion and storage. Abstract : With the facile technique in alkali hydrolysis and HF‐free electrochemical etching, MXene nanowire is fabricated in a shortened etching time without the utilization of hazardous HF acid. The MXene NW@3D substrate not only renders a boosted kinetics and shortened diffusion length, but also offers a stable hydrogen evolution activity and flexible zinc ion battery application even during the deformation progress.